Hygge: Food and the construction of safety among incarcerated women in Denmark. (1st October 2019) - Smoyer, Amy B.; Minke, Linda Kjær
Abstract: Knowledge about women's socio-emotional experience of incarceration is sparse. To address this gap in the research, open-ended interviews were conducted with 9 incarcerated women in Denmark. The inquiry focused on their experiences with prison food and eating, including questions about hygge -related practices. Hygge is a cherished part of Danish culture that encourages people to create cozy environments by sharing food and fellowship. While this warm and comforting practice may seem incongruent with prison, contemporary theory about carceral geography suggests a wide range of emotional spaces within prisons and identifies the central role of incarcerated people and external norms on constructing these spaces. The participants' narratives describe and explain the role of hygge in Danish prisons. Participants report using food and other props to construct hygge in their cells, in common areas, and with visitors, in order to build safety and manage the harshness of prison life. While these experiences are fleeting, findings suggest that the ability of these women to engage in hygge practices has a deeply positive impact on their lived experience of incarceration. The findings expand understanding about the role of food in prison and inform the practices of correctional facilities.